Effect of calorie on cognitive function among Traumatic Brain Injury (TBI) patients: a pilot study - Aryati, Ahmad; Ahmad Zubaidi, A.latif; Sharifah Wajihah Wafa, Syed Saadun Tarek Wafa (2020)
Cognitive recovery is a major concern to traumatic brain injury (TBI) patients and their caregivers as patients need to resume normal life after hospital discharge. A recent discovery showed that low calorie was beneficial for cognitive function with lower mortality rate and produced better clinical outcomes in critically-ill and medical intensive care unit patients. However, the effect of low calorie on cognitive function among TBI patients has not been determined yet. Hence this study was conducted to provide preliminary evidence of the relation between calorie and cognitive function and to determine calorie adequacy for optimal cognitive recovery among them. This pilot study involved ten patients recruited from Hospital Sultanah Nur Zahirah, Kuala Terengganu. The patients underwent a series of nutritional assessments including 24-hours diet recall combined with food diary; neuropsychology test [Montreal Cognitive Assessment (MoCA)], and eye-open-eye-close paradigm of electroencephalography (EEG) for two to six days. Socio-demography, nutritional and neuropsychology data were analyzed using SPSS version 22 with the percentage of calorie intake (%CI) was set as the independent variable; whilst duration to finish trail-making subtest (FT), and the total score (TS) of MoCA were the dependent variables. EEG data were analyzed using Fast-Fourier Transform (FFT) and power ratio (PR) which is the ratio of slow to fast frequency brain band was calculated. Then the comparison of %CI, FT, TS, and PR were done between day-1 and discharge-day (early or follow-up visit in EEG). Six male and four female patients with mild TBI, median age 28.9 years (IQR = 9.5) were included in the study. Scatter dot plot between %CI to FT and TS showed that the graph increased at the beginning before it became a plateau at 70%. The %CI had significant negative correlation with FT (r = -0.717; p = 0.000) but positive correlation with TS (r = 0.789; p = 0.000). Results revealed that cognitive function was improved at low %CI, approximately below CI of 70%. Improvement in neuropsychology test results was strengthened by the significant differences of median EEG power ratio between follow-up and first visit (p = 0.000). In this pilot study, it appears that cognitive function showed improvement with low calorie intake among TBI patients.